2016
DOI: 10.1093/treephys/tpw104
|View full text |Cite
|
Sign up to set email alerts
|

Ecophysiological responses ofBetula pendula,Pinus uncinataandRhododendron ferrugineumin the Catalan Pyrenees to low summer rainfall

Abstract: Climate change is producing modifications in the intensity and frequency of rainfall in some regions of the planet. According to predictions, annual rainfall distribution in Western Europe will result in an increase in episodes of drought, thereby negatively affecting nutrient availability. Since high mountain systems will be particularly vulnerable, the physiological and nutritional responses to changes in summer rainfall were monitored over the course of two consecutive summers on three species, which are re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…A recent ecophysiological study in the PNAESM indicated that Pinus uncinata exhibits high tolerance to variations in precipitation, while Betula pendula is particularly vulnerable to low precipitation levels, and Rhododendron ferrugineum is adversely affected by brief drought events (Fernàndez-Martínez et al, 2016). Consequently, continued drying and a potential increase in drought frequency could further solidify the dominance of black pine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent ecophysiological study in the PNAESM indicated that Pinus uncinata exhibits high tolerance to variations in precipitation, while Betula pendula is particularly vulnerable to low precipitation levels, and Rhododendron ferrugineum is adversely affected by brief drought events (Fernàndez-Martínez et al, 2016). Consequently, continued drying and a potential increase in drought frequency could further solidify the dominance of black pine.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that species richness for Ericaceae was significantly correlated with MAP, PDM, and PWM, although the relative importance of water availability in explaining the elevational pattern of richness was smaller than temperature. Rhododendron ferrugineum L. is thought to be particularly affected by short periods of scarce rainfall, which negatively affects leaf gas exchange [61]. Snow cover during winter provides protection for the plants at high elevation.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies focusing on the plasticity of LMA to abiotic factors have found that it responds to numerous changes in environmental conditions in nature; the factors driving variation in LMA include light (Coble & Cavaleri, 2015;Fajardo & Siefert, 2016), temperature (Fajardo & Piper, 2011;Zhang et al, 2020), water (Fernandez-Martinez et al, 2016;Sanchez-Gomez et al, 2013), nutrients (Onoda et al, 2008;Wang et al, 2019), and CO 2 (Hikosaka et al, 2005;Ishizaki et al, 2003). However, a meta-analysis from Poorter et al (2009) Sunlight does not only supply the essential energy input for photosynthesis (Hikosaka et al, 1994;Moss, 1967;Oguchi et al, 2017), but importantly provides cues that regulate leaf traits and dictate plant functional strategy (Ballaré, 2014;Jenkins et al, 2001;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies focusing on the plasticity of LMA to abiotic factors have found that it responds to numerous changes in environmental conditions in nature; the factors driving variation in LMA include light (Coble & Cavaleri, 2015; Fajardo & Siefert, 2016), temperature (Fajardo & Piper, 2011; Zhang et al, 2020), water (Fernandez‐Martinez et al, 2016; Sanchez‐Gomez et al, 2013), nutrients (Onoda et al, 2008; Wang et al, 2019), and CO 2 (Hikosaka et al, 2005; Ishizaki et al, 2003). However, a meta‐analysis from Poorter et al (2009) has identified that light is the dominant factor driving LMA variation, exceeding temperature in importance, based on LMA data from a total of 3800 species across functional groups and ecosystems types.…”
Section: Introductionmentioning
confidence: 99%